First record of the red lionfish, Pterois volitans, on the coast of Tabasco, Mexico - Wakida-Kusunoki, Armando T.; Amador del Ángel, Luis Enrique (HIDROBIOLÓGICA, 2016)
Two specimens of lionfish Pterois volitans were found for the first time on the south coast of Tabasco in southeastern Mexico. This was the fifth time that this fish has been located on the Mexican coast of the Gulf of Mexico. The presence of lionfish on the Tabasco coast of Mexico is discussed.